Effects of Orthokin, Sensikin and Persica mouth rinses on the force degradation of elastic chains and NiTi coil springs - Javanmardi, Zahra (J Dent Res Dent Clin Dent Prospects, 2016)
Background. Elastomeric chains and NiTi coil springs are two major traction aids in orthodontic tooth movements. Force degradation occurs over time in both groups, with higher percentages in elastic chains. The effects of environmental factors and some mouth rinses on this force decay have been previously studied. No study has been performed to evaluate the effect of current popular mouth rinses such as Orthokin, Sensikin and Persica on this force degradation. Methods. Forty pieces of elastic chains consisting of 5 loops (Ortho Technology, USA) and 40 NiTi closed coil springs (3M Unitek, Germany) were divided into 4 groups: control (artificial saliva), Orthokin mouthwash, Sensikin mouthwash and Persica mouthwash. All the groups were kept in an incubator at 37°C for 3 weeks. In the test groups, the samples were immersed in mouthwash twice a day. Force degradation was measured at 5 time intervals: baseline, 1 hour, 24 hours, 1 week and 3 weeks, using a digital force gauge. Repeated-measures ANOVA and one-way ANOVA were used for statistical analysis. Results. Force decay occurred over time in both elastic chainand coil spring groups. In elastic chain group, after 3 weeks, Orthokin mouth rinse had significantly lower force degradation compared to other groups (P < 0.05) and in coil spring group there were no statistically significant differences in force degradation after 3 weeks between the subgroups (P > 0.05). Conclusion. Based the results of this study, these three mouthwashes did not increase the force degradation of orthodontic traction aids under study.